Improving Teacher Pedagogic Competence through PKM Lessons Study - Francisca Sestri Goestjahjanti; Dewiana Novitasari; Eva Agistiawati; Sahala Benny Pasaribu; Gusli Chidir (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
Partners in this activity are teachers from one of the junior high schools in Tangerang as an effort to improve the pedagogic competence of teachers through PKM (Pengabdian Kepada Masyarakat) lesson study. More than 75% of students must take remedial final exams to meet the minimum completeness criteria. This partnership program aims to increase the knowledge of teachers about the fulfillment of students' learning rights. Based on the problems faced by partners, the solutions offered are training and lesson study assistance. The result of this activity is an increase in pedagogic competence which is marked by increasing teacher knowledge in the form of making chapter designs and lesson designs in collaboration with colleagues, as well as increasing the fulfillment of students' learning rights marked by the creation of an active, creative, effective, innovative, and fun learning atmosphere. In addition, PKM lesson study produces outputs in the form of scientific articles published in national or international journals.